2020
DOI: 10.3389/fvets.2020.00451
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Hydrolyzed Diet Supplemented With Prebiotics and Glycosaminoglycans Alters Lipid Metabolism in Canine Inflammatory Bowel Disease

Abstract: Canine inflammatory bowel disease (IBD) is a chronic, immunologically mediated intestinal disorder, resulting from the complex interaction of genetic, environmental and immune factors. Hydrolyzed diets are used in dogs with food-responsive diarrhea (FRD) to reduce adverse responses to immunostimulatory proteins. Prebiotics (PRBs) and glycosaminoglycans (GAGs) have previously been demonstrated to show anti-inflammatory activity in the intestinal mucosa. Notably, hydrolyzed diets combined with the administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…However, in another study, treatment with a novel protein diet and treatment with prednisolone for 4 weeks had a significant impact on the phospholipid profile in dogs with chronic enteropathies [ 30 ]. Additionally, a recently published study revealed an altered lipid metabolism after 10 weeks of feeding a hydrolyzed diet to dogs with chronic enteropathies [ 60 ]. Therefore, the timeframe of 70 days chosen in our study should have been sufficient to reveal a recovery of altered metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, treatment with a novel protein diet and treatment with prednisolone for 4 weeks had a significant impact on the phospholipid profile in dogs with chronic enteropathies [ 30 ]. Additionally, a recently published study revealed an altered lipid metabolism after 10 weeks of feeding a hydrolyzed diet to dogs with chronic enteropathies [ 60 ]. Therefore, the timeframe of 70 days chosen in our study should have been sufficient to reveal a recovery of altered metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expression of pro-inflammatory cytokines and antimicrobial peptides produced by Paneth cells were also identified. In addition to structural and compositional relevance, functionality was also demonstrated by these authors (Mochel et al, 2017;Chandra et al, 2019;Ambrosini et al, 2020a). In this same study, canine organoids demonstrated metabolic activity during differentiation, functional cystic fibrosis transmembrane conductive regulator (CFTR) chloride channels and uptake of exosome-like vesicles secreted by the parasite Ascaris suum (Chandra et al, 2019).…”
Section: Organoids-a Possible Solution For Translational Research In Ibdmentioning
confidence: 69%
“…Such abnormalities include a large number of IgE positive cells in dogs with cIBD ( Locher et al, 2001 ), a decrease in mast cell numbers with a concomitant increase in CD3+ cells, IgG+ plasma cells, CD11c cells and reduced Treg cells ( Jergens et al, 1996 ; Jergens et al, 1998 ; German et al, 2001 ; Kathrani et al, 2011b ; Schmitz et al, 2012 ). Furthermore, diet has also been shown to impact mucosal microbiota and the GI metabolome and mucosal microbiota in dogs with cIBD ( Atherly et al, 2019 ; Ambrosini et al, 2020a ). Recently, early-life risk factors for developing IBD have been an area of interest and studies have identified similar findings in dogs and humans with cIBD/IBD such as an association with early life high-fat low-carbohydrate diets and the later development of IBD/cIBD ( Hemida et al, 2021 ).…”
Section: Pitfalls Of Current Ibd Models–a Roadblock In Treatment Disc...mentioning
confidence: 99%
“…In the veterinary field, this subject has also been recently reported, with significant variances identified in plasmatic and whole blood phospholipid profiles of dogs with IRE and FRE [ 23 ], and in dogs with IBD after a hydrolyzed diet [ 24 ]; however, no information is available on the erythrocyte membrane lipidome. To choose the representative cell type, it must be considered that red blood cells are the largest contributors to cell numbers in the body and make up the highest number of cells formed every day [ 25 ].…”
Section: Introductionmentioning
confidence: 99%